Penerapan Nilai-Nilai Islam dalam Kehidupan Sehari-Hari Siswa SD - Aditya Dwi Lanza; Daniel Matin Nasrullah (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
The application of Islamic values in elementary schools is very important for shaping children's character from an early age. At this age, children begin to form their worldview and character. Therefore, Islamic values such as honesty, discipline, responsibility, and mutual respect are essential. These values are applied through religious activities such as congregational prayers, study circles, and group prayers. The integration of Islamic values into learning helps children understand and practice religious teachings in their daily lives, as well as instill positive values that will be useful for their future. An Islamic school culture, with the implementation of manners, courtesy, and good language, influences student behavior. Religious-based extracurricular programs, such as Islamic arts, memorization of the Qur'an (tahfidz), and Islamic sports, support the strengthening of children's character. The impact is an increase in spiritual awareness and student character, as well as improved discipline and a sense of responsibility in their daily lives. However, the main challenge is the lack of parental involvement and limited time. Therefore, collaboration between the school, teachers, and families is crucial to ensure that character education based on Islamic values runs well. With good cooperation, it is hoped that children will grow into individuals with noble character and be able to practice Islamic teachings in their daily lives. This collaboration is key to shaping a generation with good morals and faith, as well as being ready to face global challenges.